The Effectiveness of Flipbook-Based Learning Media Using Problem-Based Learning on Students’ Interest in UX Design Course - Hidayat, Wahyu Nur; Smaragdina, Azhar Ahmad; Kirana, Kartika Candra; Firmansyah, Muhammad Ferdian; Mas’udah, Ajeng Ramadhani Lailul; Akbar, Asna Isyarotul; Sari, Rahajeng Kartika (Edu Komputika Journal, 2024)
User Experience Design at the State University of Malang encounters significant challenges in students’ grasp of essential concepts such as Design Thinking, User Experience (UX), and User Interface (UI) design, primarily due to the lack of specialized learning resources. This study addresses these challenges by developing a Flipbook-based learning resource integrated with Problem-Based Learning (PBL) strategies, aiming to enhance student engagement and motivation. The research follows the Research and Development (R&D) method, utilizing the ADDIE model, which includes Analyze, Design, Development, Implement, and Evaluate phases. The resulting media, a UX Design flipbook with a .html extension, underwent rigorous validation. Material expert validation achieved a score of 81.90%, while media expert validation scored 87.82%, both categorized as very feasible. Furthermore, small and large group trials yielded very feasible ratings of 86.23% and 87.38%, respectively. The student interest test indicated a high score of 86.30%, reflecting very high student interest. These findings demonstrate that the developed media is well-suited as supplementary material in UX Design education, promoting a more interactive, engaging, and effective learning environment. This innovative approach holds promise for improving student understanding and interest in the UX Design course.